Psalm 95 and Matthew 11:25-30 - WANG, Donald (Journal of Research for Christianity in China (JRCC), 2023)
Rest is an important biblical theology theme. Psalm 95 has strong parallels with Matthew 11:25-30, and the shared literary features and theological themes show that Matthew 11:25-30 alludes to Psalm 95. The invitation of Jesus to come to him for rest is the fulfillment of the typology of Sabbath rest in the Old Testament.
Keywords: Rest, allusion, Psalm 95, Matthew 11:25-30